2004
DOI: 10.4321/s1130-01082004000700002
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life (GIQLI) and laparoscopic cholecystectomy usefulness in patients with gallbladder dysfunction or chronic non-lithiasic biliary pain (chronic acalculous cholecystitis)

Abstract: Objective: the aim of this study was to evaluate the incidence, clinical features and role of laparoscopic cholecystectomy (LC) in patients with chronic acalculous cholecystitis (CAC) in comparison with a control group of patients who underwent cholecystectomy for chronic calculous cholecystitis (CCC). Material and methods: prospective evaluation of 34 patients with CAC in contrast with 297 patients with CCC. Outcome measures: clinical presentation, quality of life using the Gastrointestinal Quality of Life In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…9 Using GIQLI, Planells et al detected significant and similar quality-of-life improvements following LC in both calculous and acalculous cholecystitis patients. 6 Using both GIQLI and SF-36, Quintana et al found that patients with symptomatic cholelithiasis and low surgical risk experienced the highest quality-of-life gains; patients with asymptomatic cholelithiasis or high surgical risk experienced least improvement. The authors concluded that LC is appropriate for patients with symptomatic gallstone and low surgical risk.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…9 Using GIQLI, Planells et al detected significant and similar quality-of-life improvements following LC in both calculous and acalculous cholecystitis patients. 6 Using both GIQLI and SF-36, Quintana et al found that patients with symptomatic cholelithiasis and low surgical risk experienced the highest quality-of-life gains; patients with asymptomatic cholelithiasis or high surgical risk experienced least improvement. The authors concluded that LC is appropriate for patients with symptomatic gallstone and low surgical risk.…”
Section: Discussionmentioning
confidence: 98%
“…5 However, there are limited researches in the literatures that have reported LC quality-of-life outcomes. [6][7][8][9][10] The quality-of-life impacts of LC and the predictors of patients' subjective outcomes remained undetermined, especially in the Asian context. The aims of this study are to use the Medical Outcomes Study 36-Item Short-Form Health Survey (SF-36) and Gastrointestinal Quality of Life Index (GIQLI) surveys to report subjective quality-oflife following LC and to investigate the factors that may predict LC quality-of-life outcomes in adults with cholelithiasis.…”
Section: Introductionmentioning
confidence: 99%
“…Anti-emetic prevention, the utilization of propofol as a rapid anesthetic inductor with minimal undesirable residual effects, and the association during anesthetic induction of NSAIDs (ketorolac) have all permitted a successful ambulatorization of LC (6,13,14), which is according to various series around 55-97% (12)(13)(14)(15). Table V shows series reported along the development of the outpatient approach, including case numbers and ambulatorization percentage (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, acceptance before the ambulatory procedure shows differences among the various degrees of information demanded according to patient age, sex, education. Such information must assure home self-management during the postoperative period, and be exhaustive in order to ensure maximal quality of care, thus avoiding the undesirable effects of surgery "without information", which originates a high percentage of complications that remain undetected by the surgical unit (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…Unexplored is the correlation of quality of life with liver enzyme measures, including serum levels of alkaline phosphatase, direct and total bilirubin, alanine aminotransferase (ALT), and aspartate aminotransferase (AST). Using general health status and gastrointestinal health-specific measuring instruments [6][7][8], the objectives of this study were to investigate the association of qualityof-life status with baseline laboratory findings and to elucidate quality-of-life predictors among Taiwanese adults undergoing surgery for symptomatic gallstone disease.…”
Section: Introductionmentioning
confidence: 99%